Development of Analytical Procedures for Lead Determination in Incense by Graphite Furnace AAS - Coco, Jessica [UNESP]; Bechlin, Marcos A. [UNESP]; Barros, Ariane I. [UNESP]; Ferreira, Edilene C. [UNESP]; Veiga, Marcia A. M. S.; Neto, Jose A. Gomes [UNESP] (Perkin-elmer Corp, 2017)
The use of incense has increased over the past years; however, few studies have been carried out concerning the quantification of toxic elements. This article describes the development of analytical methods for Pb determination in the rod and coating of incense sticks by solid sampling high-resolution continuum source graphite furnace atomic absorption spectrometry (SS HR-CS GFAAS). For comparative purposes, samples were also analyzed by line source graphite furnace atomic absorption spectrometry (IS GFAAS) after acid microwave-assisted digestion. The concentration of lead varied from 0.06 a 2.17 mu g g(-1) in the rods and 1.06 to 6.60 mu g g(-1) for the coating. A paired t-test at a 95% confidence level showed that the SS HR-CS GFAAS results were in agreement with those obtained by LS GFAAS. The precision of measurements obtained by SS HR-CS GFAAS varied from 0.5 to 16% and 1.9 to 15% for rod and coating, respectively. Also, emission of lead generated when the incense stick samples were burning was evaluated by ash analysis and the mass balance applied for total lead in the whole samples and the remaining lead in the ashes. These findings showed that 25 to 80% of the total lead content in incense may be released to the air. These large variations may be related to the type of raw materials (chemical composition) employed in incense production.